Preparation and Antibacterial Properties of Substituted 1,2,4-Triazoles - Ionuţ Ledeţi; Vasile Bercean; Anda Alexa; Codruţa Şoica; Lenuţa-Maria Şuta; Cristina Dehelean; Cristina Trandafirescu; Delia Muntean; Monica Licker; Adriana Fuliaş (Journal of Chemistry)
Background. Both 1,2,3- and 1,2,4-triazoles are nowadays incorporated in numerous antibacterial pharmaceutical formulations. Aim. Our study aimed to prepare three substituted 1,2,4-triazoles and to evaluate their antibacterial properties. Materials and Methods. One disubstituted and two trisubstituted 1,2,4-triazoles were prepared and characterised by physical and spectroscopic properties (melting point, FTIR, NMR, and GC-MS). The antibacterial properties were studied against three bacterial strains: Staphylococcus aureus (ATCC 25923), Escherichia coli (ATCC 25922), and Pseudomonas aeruginosa (ATCC 27853), by the agar disk diffusion method and the dilution method with MIC (minimal inhibitory concentration) determination. Results. The spectroscopic characterization of compounds and the working protocol for the synthesis of the triazolic derivatives are described. The compounds were obtained with 15–43% yields and with high purities, confirmed by the NMR analysis. The evaluation of biological activities showed that the compounds act as antibacterial agents against Staphylococcus aureus (ATCC 25923), while being inactive against Escherichia coli (ATCC 25922) and Pseudomonas aeruginosa (ATCC 27853). Conclusions. Our results indicate that compounds containing 1,2,4-triazolic moiety have great potential in developing a wide variety of new antibacterial formulations.